2000
DOI: 10.1084/jem.191.10.1637
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangement of Immunoglobulin Genes in Shark Germ Cells

Abstract: The variable (V), (diversity [D]), and joining (J) region recombinases (recombination activating genes [RAGs]) can perform like transposases and are thought to have initiated development of the adaptive immune system in early vertebrates by splitting archaic V genes with transposable elements. In cartilaginous fishes, the immunoglobulin (Ig) light chain genes are organized as multiple VJ-constant (C) clusters; some loci are capable of rearrangement while others contain fused VJ. The latter may be key to unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 49 publications
0
61
0
1
Order By: Relevance
“…It is now found that the cDNA sequences are all encoded by a small family consisting of one germline-joined cluster and two clusters capable of rearrangement. Together with the NS4 L chain, this is another instance where clusters with joined as well as split gene organizations of an IgL isotype has been found, supporting the idea of rare VJ recombination taking place in the shark germ cells (10). NS5 is a very small family of genes, and the same genes are carried by several sharks from the wild.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…It is now found that the cDNA sequences are all encoded by a small family consisting of one germline-joined cluster and two clusters capable of rearrangement. Together with the NS4 L chain, this is another instance where clusters with joined as well as split gene organizations of an IgL isotype has been found, supporting the idea of rare VJ recombination taking place in the shark germ cells (10). NS5 is a very small family of genes, and the same genes are carried by several sharks from the wild.…”
mentioning
confidence: 72%
“…That is, like the NS4 isotype, some NS5 loci contain split V and J gene segments that rearrange in somatic cells while others carry preassembled VJ sequences. The NS4 V genes are closely related (up to 99% identity), enabling the construction of a molecular clock to estimate dates of the recombination events that produced the six germline-joined genes; they are thought to have occurred over a period of 0 -49 million years ago (10). At 82% identity with NS5-2, the rearranged NS5-16 V gene is a member of the same family and definitely not a translocation from the NS3 or NS4 loci, but it diverged a long time ago from the NS5 split genes.…”
Section: Germline-joined Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, extant cartilaginous fish have two H chain isotypes that are expressed in lineages of B cells rather than by class switch [21,27,[37][38][39]. Thus, both the V and C domains of the L chains may have coevolved with H chains to influence L chain evolution.…”
Section: Discussion Natural History Of Four Ancient Igl Cladesmentioning
confidence: 99%
“…4), suggest that nurse shark r genes are also in the cluster configuration. Another unusual feature of shark Ig genes is the phenomenon of germline joining of V-J or V(D)J via RAG activity in germ cells [21]. In nurse shark some or all of the V-J segments are joined for each previously studied isotype.…”
Section: Gene Organization and Numbermentioning
confidence: 99%